MAKNA FILOSOFIS KEBERADAAN ORNAMEN BEDAWANG NALA DI DASAR BANGUNAN MERU - I Nyoman Widya Paramadhyaksa (Jurnal Filsafat "WISDOM", 2010)
AbstractThis study discusses philosophical meanings of bedawang nala ornaments found on foundation of meru buildings in Bali. The bedawang nala is an ornament in the form of giant turtle with fire tongue and one or two serpents coiling it. Qualitative-interpretativemethod is applied in the analysis. The results show that the bedawang nala ornament is related to the concept of Vadavamukha, the hell located at the bottom of Mount Meru, which supports the universe, and to the folklore of occurrence of earthquakes.Keywords: bedawang nala, meru.